1996
DOI: 10.1111/j.1467-8551.1996.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Learning Styles for Training and Development: A Discussion of the Matching Hypothesis

Abstract: This review paper examines the effect of matching and mismatching learning style and learning activity and matching and mismatching trainer and trainee learning style on learning achievement. It also explores the possibility of creating a match by promoting learner adaptability or modifying the trainer's training style. The implications of this discussion for training and development are considered.In a recent paper Hayes and Allinson (1994) considered the relevance of cognitive style for management practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 45 publications
3
65
1
Order By: Relevance
“…Detailed information about learning styles is also crucial when identifying relationships between learning styles and the performance of students in an online course (see Hayes & Allinson, 1996) or other characteristics of students such as cognitive traits (Graf, Lin, & Kinshuk, in press). A detailed description of the different characteristics of each dimension and how representative they are for that specific dimension of the learning style is necessary.…”
Section: Journal Of Research On Technology Inmentioning
confidence: 99%
“…Detailed information about learning styles is also crucial when identifying relationships between learning styles and the performance of students in an online course (see Hayes & Allinson, 1996) or other characteristics of students such as cognitive traits (Graf, Lin, & Kinshuk, in press). A detailed description of the different characteristics of each dimension and how representative they are for that specific dimension of the learning style is necessary.…”
Section: Journal Of Research On Technology Inmentioning
confidence: 99%
“…Witkin et al (1977) was among the first cognitive styles researchers to suggest that teaching and learning styles could be matched to improve student outcomes. Hayes and Allinson (1996) found that two of six studies using the field-dependence/independence learning style model to investigate the possible effect of matching learning styles on learning outcomes demonstrated a significant relationship. Smith believes the field dependence/independence model favors males from middle and upper class backgrounds (2002).…”
Section: Cognitive-centered Approachesmentioning
confidence: 99%
“…In an analysis of five studies completed before 1990, Hayes and Allinson (1996) found that all five indicated that there was some interaction between learning style and achievement. Wang, Hinn, and Kanfer (2001) found no significant difference between Kolb learning style groups on an achievement test taken by 31 participants following a class that used a computer program to facilitate online collaboration.…”
Section: Activity-centered Approachesmentioning
confidence: 99%
“…Does a matching of learner preference and instructional task affect learning performance? There have been some studies about the effects of matching and mismatching student learning styles and cognitive styles with instructional treatments in management (Entwistle, 1988;Hayes & Allinson, 1996), but little has been done concerning language learning. Therefore, there were several purposes for this study.…”
Section: Kata Kunci: Cognitive Style Field Dependence Field Indepenmentioning
confidence: 99%